Romeo and Juliet - Shakespeare, William, 1564-1616 (United Kingdom : Sweet Cherry Publishing Limited, 2015)
A prose retelling of William Shakespeare's play about two young people who fall in love despite their families' age-old feud.
Primary
800-899
Keywords: Shakespeare, William, -- 1564-1616; Vendetta -- Juvenile literature; Youth -- Juvenile literature; Romeo (Fictitious character) -- Juvenile literature; Juliet (Fictitious character) -- Juvenile literature; Conflict of generations -- Juvenile literature; Italy -- Verona